Prospects of AI Use in The Supreme Court: Comparison of Canada and Indonesia - Geofani Milthree Saragih; Ade Sathya Sanathana Ishwara; Jeremy Aprilian Hutauruk; Mohamad Juliandri Rahman; Mariko Hattori (Jurnal Hukum dan Peradilan, 2026)
The opportunities and challenges of applying artificial intelligence (AI) in law enforcement are the main focus of a comparative study between the Indonesian Supreme Court and Canadian judicial guidelines. In Canada, AI has been used to support transparency, speed, and consistency in decisions through decision prediction, case management, and legal data processing. This serves as an important inspiration for Indonesia, which is currently exploring the use of similar technology in its judicial system. The main challenges faced by Indonesia include limited digital infrastructure, the absence of comprehensive regulations governing the use of AI, and concerns regarding the integrity of decisions and the principle of justice. A normative juridical method combined with a comparative literature review was employed to examine the regulatory frameworks, court practices, and applications of artificial intelligence in each country. The study's findings indicate that despite the significant challenges in Indonesia, the opportunities for AI implementation remain vast. AI implementation must be supported by adaptive national policies, capacity building for judicial officials, and continuous oversight to maintain the integrity of decisions and legal certainty. This study provides strategic recommendations for strengthening Indonesia's legal system in an increasingly complex and dynamic digital era.